Regulation and physiological functions of phoenixin - Liang, Han; Zhao, Qian; Lv, Shuangyu; Ji, Xinying (Frontiers in Molecular Biosciences, 2022)
Phoenixin is a newly discovered neuropeptide generated from small integral membrane protein 20. Phoenixin is a ligand for the G protein-coupled receptor 173 (GPR173) and has been detected in central and peripheral tissues of human, rats, mice, bovine, and zebrafish. It was initially involved in regulating reproductive function by stimulating the luteinizing hormone release from pituitary cells by increasing the level of gonadotropin-releasing hormone. Recently, many functions of phoenixin have been generalized, including regulation of food intake, memory, Alzheimer's disease, anxiety, inflammation, neuronal and microglial activity, energy metabolism and body fluid balance, cardiovascular function, and endocrine activity. In addition, the interaction between phoenixin and nesfatin-1 have been revealed. The present article summarized the latest research progress on physiological function of phoenixin, suggesting that it is a potential target for novel drug development and clinical application.